2003
DOI: 10.1177/107906320301500205
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Psychological Distress in Sex Offender Therapists

Abstract: The provision of psychological services to sexual offenders presents therapists with many challenges, including exposure to vivid descriptions of sexual violence and trauma. Although there is an increasingly robust body of literature investigating the effects of such traumatic exposure on therapists who work with the victims of sexual abuse, there have been few studies of its impact on those who treat the perpetrators. This study provides an exploratory investigation of the experience of psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 7 publications
5
54
1
Order By: Relevance
“…Within the field of sex offender treatment, treatment providers are often exposed to graphic details of the offences committed by their clients. In the attempt to lessen the risk of further offending, treatment providers listen to and process the sexual content of offenders' behaviour and fantasies (Bengis, measurements of vicarious trauma report only mild (Ennis & Horne, 2003; to moderate (Kadambi & Truscott, 2003;Way, VanDeusen, Martin, Applegate, & Jandle, 2004) levels of vicarious trauma. Little information exists in relation to the factors that mediate vicarious trauma, although there is some evidence that access to supervision or peers is important (Ennis & Horne, 2003;Kadambi & Truscott, 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Within the field of sex offender treatment, treatment providers are often exposed to graphic details of the offences committed by their clients. In the attempt to lessen the risk of further offending, treatment providers listen to and process the sexual content of offenders' behaviour and fantasies (Bengis, measurements of vicarious trauma report only mild (Ennis & Horne, 2003; to moderate (Kadambi & Truscott, 2003;Way, VanDeusen, Martin, Applegate, & Jandle, 2004) levels of vicarious trauma. Little information exists in relation to the factors that mediate vicarious trauma, although there is some evidence that access to supervision or peers is important (Ennis & Horne, 2003;Kadambi & Truscott, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Whilst the primary victims of traumatic events are those with first-hand experience of the event itself, it is now being recognized that those indirectly exposed may also be affected (Ennis & Horne, 2003). Within the field of sex offender treatment, treatment providers are often exposed to graphic details of the offences committed by their clients.…”
Section: Introductionmentioning
confidence: 99%
“…With a limited number of qualified supervisors, the paucity of supportive colleagues willing to offer a listening ear, and the stigma attached to the work itself, it is small wonder that some social workers experience professional isolation (Pais 2001;Van Deusen and Way 2006). The implications of such isolation, coupled with exposure to traumatic material, have been well documented, including callousness, suspicion, hypervigilance, and vulnerability (Ennis and Horne 2003;McCann and Pearlman 1990;Pais 2001;Thorpe et al 2001). Not surprisingly, the quality of some clinicians' work has been shown to suffer as a result of these negative effects.…”
Section: Ensuring Competence In Cliniciansmentioning
confidence: 96%
“…Studies have shown that when clinicians who work with sex offenders are involved in professional peer support, which includes supervision, there is a reduction in their measured levels of distress (Ennis and Horne 2003;Pais 2001). Yet, for many social workers who work with offenders, it is a challenge to find a colleague who also works with sex offenders, who is in the same geographic area, and who would constitute an appropriate consultant.…”
Section: Ensuring Competence In Cliniciansmentioning
confidence: 97%
See 1 more Smart Citation